Analisa Temperatur Permukaan Panel Surya Terhadap Daya Keluaran Listrik Dengan Variasi Kemiringan - Selian, Mela Dewa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The need for energy sources at this time is very urgent, many kinds are needed, all kinds of things use electricity. Currently, more and more energy sources or alternative energy sources are being developed. One of them is using solar power. Utilization of solar energy is used to convert energy (solar cells) into electrical energy, which is designed to become solar panels. Solar panels are built with solar cell modules that can absorb solar energy and convert it into a source of electricity or energy that can be used in everyday life. The purpose of this research is to analyze the tilt of solar panels. Based on the calculation results, the maximum power output is 171 W and the output power is 164.16 W, the input power is 9624.58 W. Based on the calculation results, the best maximum efficiency results are obtained, namely 0.017%. Based on the results of the tilt angle analysis, the highest output temperature occurs at a tilt angle of 60°, namely 37.4 °C at 11.00 WIB, while the lowest temperature is at a tilt of 30° with a temperature of 28.5 °C. Based on the results of the tilt angle analysis, the highest output power occurs at an angle of 30° with a power of 76 watts and the lowest output power occurs at an angle of 60° with a power of 36 watts.